Sexual Dimorphism of Early Transcriptional Reprogramming in Dorsal Root Ganglia After Peripheral Nerve Injury - Chernov, Andrei V.; Shubayev, Veronica I. (Frontiers in Molecular Neuroscience, 2021)
Peripheral nerve injury induces genome-wide transcriptional reprogramming of first-order neurons and auxiliary cells of dorsal root ganglia (DRG). Accumulating experimental evidence suggests that onset and mechanistic principles of post-nerve injury processes are sexually dimorphic. We examined largely understudied aspects of early transcriptional events in DRG within 24 h after sciatic nerve axotomy in mice of both sexes. Using high-depth RNA sequencing (>50 million reads/sample) to pinpoint sexually dimorphic changes related to regeneration, immune response, bioenergy, and sensory functions, we identified a higher number of transcriptional changes in male relative to female DRG. In males, the induction of innate immune cascades via TLR, chemokine, and Csf1-receptor axis, robust regenerative programs driven by Sox, Twist1/2, Pax5/9 transcription factors were accompanied by a decline in ion channel and neurotransmitter receptor transcripts. Females demonstrated nerve injury-specific transcriptional co-activation of the actinin 2 networks. The predicted upstream regulators and interactive networks highlighted the role of novel epigenetic factors and genetic linkage to sex chromosomes as hallmarks of gene regulation post-PNI. We implicated epigenetic X chromosome inactivation in the regulation of immune response activity uniquely in females. Sexually dimorphic regulation of MMP/ADAMTS metalloproteinases and their intrinsic X-linked regulator Timp1 contributes to extracellular matrix remodeling integrated with pro-regenerative and immune functions. Lexis1 noncoding RNA involved in LXR-mediated lipid metabolism was identified as a novel nerve injury marker. Together, our data identified unique early response triggers of sex-specific peripheral nerve injury regulation to gain mechanistic insights into the origin of female- and male-prevalent sensory neuropathies.